Pelatihan Penyusunan Laporan Keuangan pada Pondok Pesantren Al I’tishom Berbasis Komputerisasi - Riyadhi, Baidhillah; Prasetyo, Henri; Fiorintari, Fiorintari; Arindya, Wida Sari; Khamim, Khamim; Kurniasih, Ninik; Farizi, Zulham Al (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Al I'tishom Islamic Boarding School Kubu Raya is a boarding school that was just established in 2020. The funds that go to Al I'tishom Islamic Boarding School for the construction of mosques, dormitories, and teachers' residences require the management to make thorough, neat, and transparent reports. . After the issuance of the Decree of the Ministry of Law and Human Rights on behalf of the Spreading Light of Science Foundation which oversees the Al I'tishom Islamic Boarding School, the Al I'tishom Islamic Boarding School Board has a new obligation, namely related to government regulations that require foundations to report financial statements. Based on these two problems, the proposed solution is to provide training in the preparation of computer-based financial reports. The purpose of this activity is to improve Islamic boarding school human resources in compiling computerized financial reports and according to accounting standards. The implementation of this activity uses a participatory approach with activity stages starting from observation/interviews for needs analysis, preparation, training, mentoring, and finalizing financial reports. The results of this activity enable Islamic boarding school HR to record financial transactions in an orderly manner, operate financial applications (Ai-Lemdik) properly, and understand the basics of accounting according to Islamic boarding school accounting standards. The conclusion of this activity shows that training must be accompanied by assistance to achieve maximum results. Islamic boarding school HR admitted that it was really helped in understanding the basics of Islamic boarding school accounting and the implementation of financial records through computerization with assistance, especially direct assistance (face to face). The use of Ai-Lemdik is very helpful for the Islamic boarding school financial team in carrying out financial bookkeeping. So that the output in the form of the financial statements of the Al I'tishom Islamic Boarding School in 2020 can be completed.